2014
DOI: 10.1073/pnas.1307345111
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of distinct mouse strains reveals kinesin light chain-1 splicing as an amyloid-β accumulation modifier

Abstract: Alzheimer's disease (AD) is characterized by the accumulation of amyloid-β (Aβ). The genes that govern this process, however, have remained elusive. To this end, we combined distinct mouse strains with transcriptomics to directly identify disease-relevant genes. We show that AD model mice (APP-Tg) with DBA/2 genetic backgrounds have significantly lower levels of Aβ accumulation compared with SJL and C57BL/6 mice. We then applied brain transcriptomics to reveal the genes in DBA/2 that suppress Aβ accumulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 46 publications
3
50
0
1
Order By: Relevance
“…A recent study found that a variant of KLC1, KLC1vE, confers increased susceptibility to amyloidogenic cleavage of APP, by an unknown mechanism [69]. The recruitment of kinesin-1 to APP via KLC1vE could alter trafficking of APP through the compartments responsible for amyloidogenic cleavage.…”
Section: Factors That Regulate the Transport Of App Also Regulate Itsmentioning
confidence: 99%
“…A recent study found that a variant of KLC1, KLC1vE, confers increased susceptibility to amyloidogenic cleavage of APP, by an unknown mechanism [69]. The recruitment of kinesin-1 to APP via KLC1vE could alter trafficking of APP through the compartments responsible for amyloidogenic cleavage.…”
Section: Factors That Regulate the Transport Of App Also Regulate Itsmentioning
confidence: 99%
“…It is also hijacked by pathogens during infection (3). Accumulating evidence suggests a key role for kinesin-1-dependent MT transport in several neurological disorders including Alzheimer's disease (4). Thus, determining the molecular basis for cargo recognition and regulation of kinesin-1 is important for understanding its role in normal cell function and disease states.…”
mentioning
confidence: 99%
“…Previously, we (Morihara et al 2014), and others (Jackson et al 2015; Ryman et al 2008; Sebastiani et al 2006), have shown that Aβ accumulation in APP Tg mice with DBA/2 genetic background was significantly lower than those with C57BL/6 and/or SJL. This fact clearly suggests that some genes in DBA/2 suppress Aβ accumulation.…”
Section: Resultsmentioning
confidence: 70%